To be in Vogue: How mere proximity to high‐status neighbors affects aspirational pricing in the U.S. fashion industry - Kim, Heeyon; Kim, Bo Kyung (Strategic Management Journal, 2022)
Abstract Research summary This article examines how proximity to high‐status neighbors enables lower‐status firms to engage in aspirational pricing. While prior studies have focused on associations based on bilateral agreements, we argue that mere spatial proximity to other high‐status firms creates perceived associations, which positively affects the focal firm's aspirational pricing. Furthermore, middle‐status firms are most likely to engage in aspirational pricing because they are sufficiently similar to high‐status neighbors to expect assimilation, not contrast, effects. Our multi‐method approach based on panel data from the U.S. Vogue magazine and an experiment provides converging evidence for our arguments. Being somewhat randomly featured near the advertisements of prominent high‐status firms in Vogue positively impacts the subsequent average listed price of the focal firm's products, especially for middle‐status firms. Managerial summary High‐status firms tend to form relationships with other high‐status counterparts, making it difficult for lower‐status firms to ascend the status hierarchy and access status‐based benefits. This study shows that lower‐status firms may be able to obtain status‐based benefits, namely the ability to set higher prices for their products, by merely being proximate to other high‐status firms. Our analyses using data from Vogue magazine and online experiment show that having advertisements appear proximate to those of high‐status fashion firms enables the focal firm, especially middle‐status ones, to raise the prices of their products. As advertisement locations are somewhat random in that firms do not have control over determining their adjacent ads, our study highlights that lucky locations can sometimes be beneficial to disadvantage lower‐status firms.